2017
DOI: 10.1002/ijgo.12089
|View full text |Cite
|
Sign up to set email alerts
|

Association between timing of elective cesarean delivery and adverse outcomes among women with at least two previous cesareans

Abstract: Among women with multiple cesareans, delivery at 37 weeks was associated with increased risk of neonatal respiratory morbidity and decreased risk of neonatal jaundice, but not with a reduction in maternal complications, as compared with delivery at 38 weeks or later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…We concluded that performing repetitive CS at 39 weeks induces neonatal benefits. In agreement with the present study, Hamadneh et al [14] mentioned that CSs performed at 37 weeks had a higher risk of neonatal respiratory morbidity versus those at 38 weeks. The risk of stillbirth in later gestational weeks is an important factor in deciding the appropriate timing for an elective CS at term.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We concluded that performing repetitive CS at 39 weeks induces neonatal benefits. In agreement with the present study, Hamadneh et al [14] mentioned that CSs performed at 37 weeks had a higher risk of neonatal respiratory morbidity versus those at 38 weeks. The risk of stillbirth in later gestational weeks is an important factor in deciding the appropriate timing for an elective CS at term.…”
Section: Discussionsupporting
confidence: 93%
“…A retrospective study in which 9.4% (83/886) of the patients had four or more cesarean sections reported no significant differences in terms of maternal outcomes between CSs performed at 37 and 38 weeks [14];…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 Multiple caesarean sections have been linked to an increased risk of placenta previa, uterine scar dehiscence, bladder, bowel, and ureteric injuries, abdominal wall adhesions, and uterine rupture. 5 Although C-sections are a life-saving mode of delivery for mothers and neonates, with time, it is becoming a trend to avoid the normal delivery modes. Many complications are associated with Csections in further pregnancies.…”
Section: Introductionmentioning
confidence: 99%